2020
DOI: 10.1002/mpr.1821
|View full text |Cite
|
Sign up to set email alerts
|

Critical consideration of assessment methods for clinically significant changes of mental distress after psycho‐oncological interventions

Abstract: ObjectivesConsidering the heterogeneity of cancer entities and the associated disease progression, personalized care of patients is increasingly emphasized in psycho‐oncology. This individualization makes the use of measurements of individual clinically significant change important when studying the efficacy and effectiveness of psycho‐oncological care. Two conceptualizations for the measurement of clinical significance are critically contrasted in this study: the Reliable Change Index (RCI) and the Minimal Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Data from several studies support a minimally clinically important difference of 1.5–2. 44 , 45 The current study demonstrated an absolute improvement of 3.8 in this score, with a relative improvement of 26%. A similar relative improvement of 22% was seen in the PSS.…”
Section: Discussionsupporting
confidence: 55%
“…Data from several studies support a minimally clinically important difference of 1.5–2. 44 , 45 The current study demonstrated an absolute improvement of 3.8 in this score, with a relative improvement of 26%. A similar relative improvement of 22% was seen in the PSS.…”
Section: Discussionsupporting
confidence: 55%
“…A minimal important difference (MID) for change in the hospital anxiety and depression scale score has not been determined in a population of adults with overweight and obesity. The minimal important difference in alternative populations (adults with cancer, cardiovascular disease, bronchiectasis, and chronic obstructive pulmonary disease) has most commonly been defined as a change of 2 points [ 32 , 33 , 34 , 35 , 36 ]. Therefore, we categorized changes in depression/anxiety as “decrease in symptoms” (≤−2), “no change in symptoms” (−1.99 to 1.99), or “increase in symptoms” (≥2) in the multinomial regression models.…”
Section: Methodsmentioning
confidence: 99%
“…In our samples, similar internal consistencies were obtained ( α = .8479 for the anxiety and α = .824 for the depression scales). A score of 10 or more on HADS total scale resulted useful for screening significant distress in a Spanish sample, 29 and a change of ≥2 points has been used as a cut‐off point to assess the clinical change 30 …”
Section: Methodsmentioning
confidence: 99%